2018
DOI: 10.1016/j.jcrc.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Combined vitamin C, hydrocortisone, and thiamine therapy for patients with severe pneumonia who were admitted to the intensive care unit: Propensity score-based analysis of a before-after cohort study

Abstract: Combined vitamin C, hydrocortisone, and thiamine therapy may benefit patients with severe pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 50 publications
1
106
1
7
Order By: Relevance
“…al día durante 7 días. Por otro lado, el grupo de expertos en el tratamiento clínico de la enfermedad por COVID-19 de Shanghái ha recomendado incluir altas dosis diarias de vitamina C en pacientes críticos afectados por SARS-CoV-2, debido a que su uso continuo parece lograr además una mejora significativa en el índice de oxigenación 32 . Algunos hospitales ya han incorporado al esquema de tratamiento de azitromicina e hidroxicloroquina la vitamina C i.v.…”
Section: Neumonía Y Sdraunclassified
“…al día durante 7 días. Por otro lado, el grupo de expertos en el tratamiento clínico de la enfermedad por COVID-19 de Shanghái ha recomendado incluir altas dosis diarias de vitamina C en pacientes críticos afectados por SARS-CoV-2, debido a que su uso continuo parece lograr además una mejora significativa en el índice de oxigenación 32 . Algunos hospitales ya han incorporado al esquema de tratamiento de azitromicina e hidroxicloroquina la vitamina C i.v.…”
Section: Neumonía Y Sdraunclassified
“…In septic shock patients, thiamine was associated with improved lactate clearance and a reduction in mortality [19]. These findings have led to recent observational studies, which demonstrated that sepsis patients experienced a substantial survival benefit after receiving vitamin C, hydrocortisone, and thiamine (which we will refer to as a "vitamin C protocol") [20,21]. Several randomized controlled trials are currently underway to evaluate the effects of a vitamin C protocol on clinically important outcomes in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published RCT carried out in the USA in 167 patients with sepsis-related ARDS indicated that administration of 15 g/day of IV vitamin C for 4 days may decrease mortality in these patients [3]. An earlier IV vitamin C trial of patients admitted to the ICU with pneumonia included hydrocortisone administration [4], however, systemic corticosteroid treatment has not been shown to have significant benefits in patients with COVID-19 [5].…”
mentioning
confidence: 99%